Evaluation of physical properties and bactericidal efficacy of chemically developed undoped and Mn (5, 10, 15wt%) doped ZnO nanoparticles. (16th April 2022) - Sivasankari, R.; Elango, M.; Varuna, J.; Thamizharasan, K.
ABSTRACT: Chemical precipitated and followed by calcinations is a versatile process for synthesising undoped ZnO and Mn (5, 10 and 15 wt%) doped ZnO nanoparticles at pH-10 and calcinations temperature of 450°C for 2 hours were followed for synthesising all the samples. The structural properties evaluated via XRD pattern revealed the hexagonal wurzite phase and with the grain size of 19 to 9 nm. Variation in the microstructural properties as function of dopant concentration was attributed using standard relations. The morphological and cross verification of structural properties were made via HRTEM analysis. Wide, direct allowed band gap property and narrow size distributed particles nature were confirmed through UV-visible absorption spectra with blue shifted peaks. The bandgap values got increased on increasing the dopant concentration. The presences of functional groups of the prepared samples were also confirmed by FTIR. Bands below 700 cm −1 assigns the Metal-oxygen framework of the sample. The antibacterial efficiency of the prepared nanoparticles was evaluated for gram positive bacterial strains namely Staphylococcus aureus and Bcaillus subtilis.